2005
DOI: 10.1111/j.1468-3156.2005.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐behaviour formulation for three men with learning disabilities who experience psychosis: how do we make it make sense?

Abstract: Cognitive-behaviour therapy (CBT) is increasingly being used with people with learning disabilities. One of the challenges in working this way is effectively sharing and understanding the formulation of the client's problem. One could argue that only with a shared understanding can there be collaboration between the therapist and the client. By utilizing current theory around CBT for psychosis and CBT for people with learning disabilities a diagram that was understandable to the client was developed to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Fernando and Medlicott () discussed the development of an analogy which was meaningful for the client, and Bishop and Henry () reported conceptualizing the technique of thought challenging as that of a detective looking for clues. Using the clients own language was reported by Kirkland (). Studies also reported simplification of written and verbal language, for example by using accessible information sheets (Atnas & Lippold, ; Wright, ) and reducing the need for written psycho‐educational materials (Kellett et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Fernando and Medlicott () discussed the development of an analogy which was meaningful for the client, and Bishop and Henry () reported conceptualizing the technique of thought challenging as that of a detective looking for clues. Using the clients own language was reported by Kirkland (). Studies also reported simplification of written and verbal language, for example by using accessible information sheets (Atnas & Lippold, ; Wright, ) and reducing the need for written psycho‐educational materials (Kellett et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…1997) and two case series (Haddock et al. 2004; Kirkland 2006) are evident in the current literature.…”
Section: Cognitive‐behavioural Therapy and Intellectual Disabilitymentioning
confidence: 89%
“…There have also been studies of adaptations to CBT to increase effectiveness for people with severe mental health problems including psychosis and cognitive impairments (e.g. Leggett, 1997;Collerton & Dudley, 2004;Wragg & Whitehead, 2004;Kirkland, 2005;Haddock et al 2004;Favrod et al 2007;Barrowcliff, 2008).…”
Section: What Evidence Is There For 'Accessible' Cbt?mentioning
confidence: 99%
“…In the work with Sam, photos of churches and priests were used to assess the nature and intensity of current and past distress and associated thoughts, dreams, voices and beliefs, along with a card sort for sorting pictures into OK/not OK, and a 'thermometer' card sort (low, medium, high) for rating intensity of distress. Formulations were developed, shared and explored using visual representations and included 'Circles of Worry' and 'Circles of Coping'; Kirkland's (2005) visual formulation framework developed from the case series of Haddock et al 2004 with circles containing individuals' antecedents, beliefs and consequences. The circles can be expanded/reduced to illustrate changes in degree of feeling and/or certainty in the belief(s).…”
Section: Evidence-/practice-based Adapted Approachesmentioning
confidence: 99%